Análise comparativa da atividade anti-inflamatória e antioxidante entre a curcumina pura e curcumina nitrada encapsuladas em PVP - Alves, Eduardo Makyama (2023)
Curcumin is a crystalline polyphenol present in turmeric (used in traditional medicine, food coloring and seasoning in some countries) that has some beneficial activities for humans, such as antibacterial, antioxidant and anti-inflammatory activities, but has some limitations because of its structure is hydrophobic, thermally unstable, among other factors. As a way to enhance the beneficial activities of curcumin, the aim was to add the nitro group to its structure. The nitration of aromatic compounds is a known reaction used in industrial chemistry. Therefore, this research aimed to compare the antioxidant and anti-inflammatory activity of pure and nitrated curcumin, with the aim of assisting research related to the use of curcumin as a treatment and reduction of oxidative stress. Initially, the electrophilic aromatic substitution reaction was carried out to carry out the nitration of curcumin. To confirm the desired product, thin layer chromatography analysis was performed, as well as IR and UV-Vis analyses. Then, pure and nitrated curcumin were encapsulated to improve the performance of curcuminoids, as they are soluble in water, improving their dispersion and bioactivity. Analyzes were also carried out with the encapsulated materials using SEM, DSC and encapsulation efficiency. After encapsulation, the effect of reducing oxidative stress was evaluated by evaluating the percentage of antioxidant activity with methanolic DPPH solution, evaluating the ability to inhibit lipid peroxidation of the homogenate obtained from egg yolk and analyzing the anti-oxidation activity. inflammatory process due to the denaturation of ovalbumin, the results of which were statistically analyzed. As a result of the synthesis, characteristic peaks of the formation of the nitro group in the product (nitrated curcumin) were observed in the IR spectrum and a change in the reading of the UV-Vis spectrum, as well as in the thin layer chromatographic analysis. Encapsulation was performed satisfactorily, resulting in a high percentage of encapsulation. Furthermore, the performance of curcumins (pure and nitrated) in the analyzes of oxidative stress reduction by DPPH, lipid peroxidation and ovalbumin denaturation demonstrated that both molecules have similar performance. Therefore, it can be said that curcumin's performance was improved by the encapsulation process and can be used as an alternative treatment to reduce oxidative stress, in addition to presenting antioxidant and anti-inflammatory activity that contributes to research involving the same topic in the future.